In-store Customer perception and buying behavior towards home furniture- Development of Conceptual Model - Venkatesh S. Amin; Anil Kumar, (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: Intellectually a paper that aims at developing a conceptual model that identifies customer perception and buying behavior of customers while buying home furniture. Home furniture is an individual family choice where all family members are involved in the buying process. The buying process changes when the needs of the family change and the buying behavior makes a difference in the process of buying a product that suits all the family members of a family. Hence the buying behavior of people and their preference of brand shapes the customer preference of in-store buying and a thought process of conceptual model is based on literature review and established theories of customers Design: Data from secondary sources is sourced from various publications, textbooks, and various journal papers engaging various search engines such as ResearchGate SSRN, Base, Semantics, and Inflibnet. Various points and statements, postulates, and a variety of affecting factors to customer perception is written engaging a dedicated group that is a focus group interaction method. Findings: This field of study identified various determining points for customer utility of in-store customer perception such as perceptional benefits, past feelings experience, subjective based norms, and system quality which are proposed to influence the attitude and perception of the customers Originality: This paper highlights the various affecting factors influencing the customer’s preference to use instore purchases of home furniture Paper type: Development of conceptual model based on a review of Literature.